PENGGUNAANÃÂ INSTRUCTIONALÃÂ MATERIALSÃÂ ÃÂ UNTUKÃÂ MENINGKATKANÃÂ PEMAHAMANÃÂ MAHASISWAÃÂ ÃÂ TENTANGÃÂ SISTEMÃÂ BAHANÃÂ BAKARÃÂ ELECTRONICÃÂ FUELÃÂ INJECTIONÃÂ ÃÂ - MaulanaÃƒÂ‚Ã‚Â , SonikaÃƒÂ‚Ã‚Â ; Widjanarko, DwiÃƒÂ‚Ã‚Â ; WahyudiÃƒÂ‚Ã‚Â , - (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
Penelitian ini bertujuan untuk menyusun ÃÂ Instructional ÃÂ Materials ÃÂ dan meningkatkan pemahamanÃÂ mahasiswa ÃÂ tentang penggunaannya pada ÃÂ sistem Electronic Fuel ÃÂ injection pada mata kuliah Perakitan otomotif ÃÂ II.ÃÂ Desain penelitian adalah quasi experiment dengan pre dan pos ÃÂ tes. Populasi penelitian adalah mahasiswa TeknikÃÂ Mesin Unnes yang mengikuti mata kuliah Perakitan otomotif ÃÂ II yaitu ÃÂ sejumlah 42 orang yang ÃÂ terbagi dalam duaÃÂ kelompok. Hasil penelitian menunjukkan adanya peningkatan pemahaman mahasiswa tentang sistem vahan bakarÃÂ EFI setelah menggunakan Instructional Materials. Hasil belajar rataÃ¢â¬Ârata pre tes ÃÂ adalah 60,92 dan rataÃ¢â¬Ârata pos tesÃÂ adalah 77,83. Dengan demikian terjadi peningkatan hasil belajar belajar sebesar 27,77% jika dibandingkan denganÃÂ sebelum menggunakan Instructional Materials pada sistem bahan bakar EFI.ÃÂ This ÃÂ research ÃÂ aims ÃÂ to ÃÂ create ÃÂ Instructional materials ÃÂ and ÃÂ to ÃÂ increase ÃÂ students ÃÂ understanding of ÃÂ lessonÃÂ about ÃÂ the ÃÂ use ÃÂ instructional ÃÂ materials ÃÂ and ÃÂ the ÃÂ fuel ÃÂ system ÃÂ Electronic ÃÂ Fuel ÃÂ Injection ÃÂ (EFI) ÃÂ in ÃÂ the ÃÂ AutomotiveÃÂ Assembly II lecture, Mechanical Engineering students of State University of Semarang in 2009/2010. ÃÂ The researchÃÂ used a quasiÃ¢â¬Âexperimental design; it is preÃÂtestÃÂpostÃÂtest design. The population of this research was students whoÃÂ took ÃÂ the ÃÂ Automotive ÃÂ Assembly ÃÂ II ÃÂ lecture, ÃÂ Mechanical ÃÂ Engineering ÃÂ Department, ÃÂ Semarang ÃÂ State ÃÂ UniversityÃÂ consisting of 42 students in two different group. Because there was only one class for this lecture, all students fromÃÂ the class were chosen to be population. The result of analyzed data is that there is improvement in the fuel systemÃÂ Electronic Fuel Injection (EFI) understanding after the use of ÃÂ the instructional materials for Automotive AssemblyÃÂ II lecture. The average value before using instructional materials (preÃ¢â¬Âtest) was 60.92 and the average value afterÃÂ using ÃÂ instructional ÃÂ materials ÃÂ (postÃ¢â¬Âtest) ÃÂ was ÃÂ 77.83. ÃÂ Therefore, it can be stated that the use of instructionalÃÂ materials EFI fuel system has been well and effective in accordance with studentsÃ¢â¬â¢ achievements. The achievementsÃÂ mentioned ÃÂ here ÃÂ are ÃÂ the ÃÂ achievements ÃÂ of ÃÂ students who ÃÂ joined ÃÂ the ÃÂ Assembly Automotive ÃÂ II ÃÂ lecture ÃÂ in which ÃÂ theÃÂ achievements ÃÂ value ÃÂ was ÃÂ improved ÃÂ from ÃÂ 27.77%; ÃÂ the ÃÂ percentage ÃÂ before ÃÂ using ÃÂ instructional ÃÂ materials ÃÂ EFI ÃÂ fuelÃÂ system.Keywords: instructional materials, electronic fuel injection (EFI)